Catholicism in the Changing Religious Field of Latin America: A Mapping - Jakob Egeris Thorsen (Religions, 2023)
This article presents a mapping of the changing religious landscape of Latin America, specifically focusing on the place of Catholicism therein. It explores how the varying forms of Catholicism in Latin America reflect a reality of mixed modernities, described as “tiempos mixtos” (Waldo Ansaldi), where elements of pre-modern, modern, and late modern worldviews and values are intertwined in ways very different from those of the North Atlantic West. By applying the modernization and secularization theories of David Martin and Charles Taylor and the sociology of religion of Pierre Bourdieu to the Latin American context, this article takes the first step to developing an explicatory map that can help us better understand changes within the religious field in Latin America today and the role of both popular and institutional Catholicism therein.